SPIR II/HER+ Sustainable Land Management evaluation - Billings, Lucy; Gilligan, Daniel O.; Kalva, Parthu; Leight, Jessica; Tambet, Heleene; Bahiru, Kibret Mamo; Mulford, Michael; Bekele, Kalkidan (2023)
Lucy Billings, Dan Gilligan, Parthu Kalva, Jessica Leight, Heleene Tambet, Kibret Mamo Bahiru, Michael Mulford and Kalkidan Bekele REGIONAL WORKSHOP SPIR II Learning Event Co-organized by IFPRI, USAID, CARE, ORDA, and World Vision MAY 16, 2023 - 9:00AM TO MAY 17, 2023 - 5:00PM EAT